Learning, Work and Practice: New Understandings
VIII, 224 p.
Keywords: This book’s original contribution to a crowded literature on work and learning will attract strong international interest. Its focus on the philosophy of learning at work brings a fresh perspective on a topic normally viewed through psychological, anthropological and sociological eyes. It assembles a host of internationally recognized scholars who reflect on the various philosophies of work-based learning. Full of distinctive and original contributions that provide perceptive insights into the subject, the work will be a practical support to teachers, trainers and researchers at the same time as it gives readers a clear philosophical grounding in learning at work. It is, however, not simply a book about philosophy, but a gazetteer of approaches to education in work that will sustain and inspire those who provide, engage in, and support the learning of new knowledge and skills in the workplace. With adaptability to new employment opportunities so vital to existing workers, the authors stand behind continued provision of work-based learning in the face of tightening economic constraints.